Linking between sequence stratigraphy and reservoir quality of Abu Madi Formation utilizing well logging and seismic analysis at Abu Madi and El Qar’a fields, Nile Delta, Egypt - S. Shebl; M. Ghorab; A. Mahmoud; T. Shazly; Abeer A. Abuhagaza; A. Shibl (Egyptian Journal of Petroleum)
This work has been carried out to interpret the link between sequence stratigraphy of the incised valley deposits with the reservoir quality in the Abu Madi Formation in the Abu Madi and El Qar’a Fields, onshore Nile Delta, Egypt based on borehole and seismic data. The distribution of sand-body in the Abu Madi Formation revealed that the fluvial channel sandstones are not randomly distributed but are controlled by the fluctuation of the sea level (regression and transgression). Interpretation of sandstones distribution of the Abu Madi incised-valley within a sequence stratigraphic framework allows a better understanding of their characterization during burial. The Abu Madi Formation is made up of two sequences: the lower sequence-1 (SQ 1) and upper sequence-2 (SQ 2). Sequence-1 forms the basal part of the Abu Madi Formation. It consists of two systems tracts in all the studied wells, in which the lowstand systems tract is overlained by a transgressive systems tract (TST-1), except at AM-12 and AM-15 wells in the western and eastern sides of the studied area, respectively where it consists of only transgressive system tract (TST-1). The upper sequence-2 (SQ2) is recorded in all the studied wells except at AM-12 and AM-15 wells. It is composed of two systems tracts (LST-2 and TST-2); the lower lowstand systems tracts contains thin sandstone channel-fill interpreted as LST-2, above this sandstone channel-fill the tidal deposits interpreted as TST-2. The lowstand systems tracts of the studied Abu Madi Formation is considered good reservoir target in the studied area, its porosity ranged from 15 to 22%. It was formed due to a rapid fall in relative sea level below the shelf edge formed valley incision due to subaerial exposure of the continental shelf. The floodplain deposits of TST represent a good seal separating LST reservoirs and water bearing zone of lower sequence (SQ1) and upper sequence (SQ2) in each well. Keywords: Sequence stratigraphy, Abu Madi Formation, Well logging and seismic stratigraphy, Abu Madi and El Qar’a fields